Espaços de pobreza e mobilidade urbana: os deslocamentos da população de baixa renda em Natal/RN - Morais, Tamms Maria da Conceição (2010)
This dissertation is an attempt to understand how families with an income of up to three minimum wages and living in different Areas of Demographic Expansion (AEDs) of Natal municipality specifically in the districts of Igapó and Salinas (North Administrative Zone of the city), Ponta Negra (South Administrative Zone), Santos Reis, Praia do Meio, Areia Preta and Mãe Luíza (East Administrative Zone) and Felipe Camarão (West Administrative Zone) solve their problems of urban mobility. It is, therefore, a reflection upon the mobility needs of poor urban households as expressed in terms of origin-destiny displacements for specific movements (house-work, house-school, house-shopping, house-healthcare and house-leisure), all of which being analyzed within the relationship between public transportation and poverty spaces of the city. In order to develop the study, theoretical aspects and themes related to the production of the urban space, to social and spatial segregation, to urban mobility and to transportation were confronted with the collected data referring to the urban population previously selected. One of the research main findings is the crucial role mobility plays in the social differentiation of such people living in Natal and that any policy for the improvement of their living conditions must take mobility issues into account